The value of D-dimer-albumin ratio as a prognostic biomarker in critically ill patients with sepsis: A retrospective single-center study - Jinhui Zhang; Chao Song; Zhenkui Hu (Heliyon)
Background: This study aimed to examine the potential prognostic significance of the D-dimer-albumin ratio (DAR) in critically ill patients with sepsis. Methods: A retrospective cohort study was carried out at the Affiliated Hospital of Jiangsu University, involving 1123 patients diagnosed with sepsis from January 2015 to November 2023. The patients were categorized into four groups (Q1-Q4) based on their DAR levels. The primary outcomes measured were in-hospital mortality and ICU mortality. Survival analysis was conducted using Kaplan-Meier survival curves and the log-rank test. Additionally, Cox proportional hazards regression models were utilized to investigate the relationship between the DAR and all-cause mortality. Results: The study population had a median age of 75 years (interquartile range: 65–84), and the median DAR was 0.15 (interquartile range: 0.08–0.32). The rates of hospital mortality and ICU mortality were 33.7 % and 31.9 % respectively. There was an observed increase in the cumulative incidence of 30-/60-day mortality with higher DAR levels (log-rank test, P < 0.001). After accounting for other variables, the results from multivariable Cox proportional hazards analyses demonstrated that DAR independently predicted hospital death [HR (95%CI): 1.419 (1.205–1.670); P < 0.001] and ICU death [HR (95%CI): 1.437 (1.219–1.693); P < 0.001]. Conclusions: The DAR was found to be an independent predictor of all-cause mortality in critically ill patients with sepsis.